PENGARUH IDEALISME, PENGALAMAN, DAN KOMITMEN PROFESIONAL PADA PEMBUATAN KEPUTUSAN ETIS KONSULTAN PAJAK TERDAFTAR DI WILAYAH BALI-NUSA TENGGARA - Harmana, Made Dwi; Wirakusuma, Made Gede; Wirama, Dewa Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.10.TAHUN 2017, 2017)
This study aims to determine the influence of idealism, experienceiand professional commitment to ethical decision-making of registered tax consultant in the territory of Bali-Nusa Tenggara. This study uses primary data that based on respondent’s answers on questionnaires that were distributed to 114 Registered Tax Consultant in the Territory of Bali-Nusa Tenggara. Sampling technique used is purposive sampling. The population uses all member of IKPI (Association of Tax Consultants Indonesia) Bali-Nusa Tenggara region as many as 114 people and based on criteria, specified number of samples are 90 people. The analysis shows that the idealism, experience, and professional commitment have positive impact to ethical decision making of registered tax consultant.
Keywords: Idealism, Experience, Commitment Professional, Ethical Decision